PENDIDIKAN BEBAS BIAYA DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH/MADRASAH - Sri Winarsih (IAIN Ponorogo, 2014)
Abstract: Cost isflow of resource, calculated in set of monetary which released to buy or pay inventory,service, labor,product, equipment and other goods, used for business or others interest. Education is process where someone obtain to get knowledge (knowledgeacquisition), developing skill or ability (development skill) attitude or change attitude. Education is a process of student’s transformationin order to reach certain things as effect of follow education. Cost of education consist of (1).Direct cost is the expense from parent to learn, example: cost of the text book,practice etc.(2).Indirect costis the expense from parent, people or governmentwhich indirect relate to learning process, for example: levyingthe building, public utilities, canteen, school health unit, etc.ملخص: التكاليف هي الموارد المحسوبة في حساب العملة المتصرفة للبيع أو دفع الأشياء المعدة، والعمل، والعمّال، والانتاج، والأدوات، وغيرها من الأشياء المستعملة لمصلحة التجارة أو غيرها. والتربية هي عملية يحصل فيها المرء على المعارف والمعلومات، وتنمية استعداداته وكفاءاته، وسلوكياته. والتربية كذلك عملية اصلاح التلاميذ ليحصل على الأشياء الخاصة نتيجة عملية التربية التي اتبعها. وثمة تكاليف تربوية وهي : 1) التكاليف المباشرة، هي التكاليف التي دفعها الطالب أو والداه لمهمة عملية التعلم والتعليم، وعلى سبيل المثال لشراء الكتب، والتربية التدريبية وغيرها، 2) التكاليف غير المباشرة، وهي التي يدفعها الطالب أو والداه، أو المجتمع، أو الحكومة للمهمة التي لا ترتبط مباشرة بعملية التعلم والتعليم، مثل التكاليف لبناء المدارس، أو الوسائل العامة، أو المقصف للمصدرسة، أو عيادة الصحة وغيرها. Keywords: Pendidikan, bebas biaya, mutu, sekolah.